Vallört som växtnäringskälla - Brusling, Anna (2007)
Russian comfrey, Symphytum x uplandicum, was tested as a plant nutrient source in a trial with tomatoes. Comfrey liquid was produced by Stiftelsen Holma i Höör. Tomato plants of the cultivar Aromata planted in a medium of soil:peat (1:1) enriched with organic nutrients and lime, were fed with comfrey liquid plus Biofer, in three different concentrations. Two different concentrations of BioRika were used as comparison, along with an unfertilized control group. In the comfrey treatment I a total amont of 1g N, 0,23 g P, 0,84 g K, was given to the tomatoes. In comfrey treatment II they were given 1,3 g N, 0,3 g P, 1 g K, and in comfrey treatment III they were given 1,7 g N, 0,4 g P och 1,9 g K. In the two treatments with BioRika the tomatoes were given 0,23 g N, 0,08 g P, 0,3 g K and 0,44 g N, 0,15 g P, 0,6 g K, respectively. The treatments were given at 11 occasions, starting when the tomatoes were 34 days and ending when they were 64 days old. The treatments gave a significant effect on the fresh weight, water content/dry matter, pH and conductivity, as the unfertilized control group differed considerably from the fertilized groups. No significant differences between the comfrey treatments and the BioRika treatments appeared during the short experimental period.